Induction of autophagy and autophagy‐dependent apoptosis in diffuse large B‐cell lymphoma by a new antimalarial artemisinin derivative, SM1044 - Cheng, Chunyan; Wang, Tao; Song, Zhiqun; Peng, Lijun; Gao, Mengqing; Hermine, Olivier; Rousseaux, Sophie; Khochbin, Saadi; Mi, Jian‐Qing; Wang, Jin (Cancer medicine (Malden, MA), 2018)
Diffuse large B‐cell lymphoma (DLBCL) is the most common form of non‐Hodgkin's lymphoma. R‐CHOP is currently the standard therapy for DLBCL, but the prognosis of refractory or recurrent patients remains poor. In this study, we synthesized a new water‐soluble antimalarial drug artemisinin derivative, SM1044. The treatment of DLBCL cell lines with SM1044 induces autophagy‐dependent apoptosis, which is directed by an accelerated degradation of the antiapoptosis protein Survivin, via its acetylation‐dependent interaction with the autophagy‐related protein LC3‐II. Additionally, SM1044 also stimulates the de novo synthesis of ceramide, which in turn activates the CaMKK2–AMPK–ULK1 axis, leading to the initiation of autophagy. Our findings not only elucidate the mechanism of autophagy‐dependent apoptosis in DLBCL cells, but also suggest that SM1044 is a promising therapeutic molecule for the treatment of DLBCL, along with R‐CHOP regimen. Our research reported an artemisinin derivative, SM1044, induces autophagy‐dependent apoptosis which is triggered by an increased acetylation of Survivin, a modification which induces its interaction with LC3‐II and its degradation. We also unraveled that the activation of CaMKK2–AMPK–ULK1 axis was molecular basis of SM1044‐dependent stimulation of autophagy. These investigations not only point to SM1044 as a promising molecule in fighting diffuse large B‐cell lymphoma (DLBCL), but also unravel important information of the molecular pathways involved in the oncogenesis of DLBCL.